1983
DOI: 10.1002/hlca.19830660318
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon Zip Reaction: A Method for Expanding Carbocycles

Abstract: SummaryA general method for enlargement of carbocyclic rings by the so called zip reaction is given. The Michael adducts of 2-nitrocycloalkanones with 3-0x0-4-pentenoates in the presence of tetrabutylammonium fluoride give in high yield compounds with the ring enlarged by four C-atoms. By this method 7-, 8-, and 12-membered cycloalkanones were converted respectively to 11-, 12-, and 16-membered functionalized carbocycles (see Scheme 2 and 3).In the last few years a large number of natural products with medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 16 publications
0
27
0
3
Order By: Relevance
“…26a was unambiguously determined by NOE experiments, which showed a 4% signal enhancement at axial proton 3-H when 1-H was irradiated. After extensive experimentation, it was found that replacement of DBU by nBu 4 NF [28] gave adducts 26a and 26b as a 1:1 mixture of isomers in a combined yield of 68%, in a more reproducible manner. The stereochemical outcome of the key Michael addition has been demonstrated to be the result of kinetic control since separated isomers were recovered unchanged when re-exposed to the reaction conditions (Scheme 3).…”
Section: Resultsmentioning
confidence: 97%
“…26a was unambiguously determined by NOE experiments, which showed a 4% signal enhancement at axial proton 3-H when 1-H was irradiated. After extensive experimentation, it was found that replacement of DBU by nBu 4 NF [28] gave adducts 26a and 26b as a 1:1 mixture of isomers in a combined yield of 68%, in a more reproducible manner. The stereochemical outcome of the key Michael addition has been demonstrated to be the result of kinetic control since separated isomers were recovered unchanged when re-exposed to the reaction conditions (Scheme 3).…”
Section: Resultsmentioning
confidence: 97%
“…Im ersten Schritt wird ein geeignet substituiertes [6] 13-bzw. 12-gliedriges Cycloalkanon-Derivat durch Ringerweiterung urn vier Glieder zum 17-bzw.…”
Section: Discussionunclassified
“…Nach Zugabe von 20 ml H 2 0 wurde rnit CH2C12 extrahiert, der Extrakt getrocknet, eingedampft und der Ruckstand chromatographiert (CH,CI,/MeOH 98:2): 1,16 g (55%) 7, farbloses 0 1 . IR: 1625IR: , 1600IR: , 1545IR: , 1330IR: , 1155IR: , 1090 ,6;143,3;143,l;142,8;137,O;136,6;135,9;135,7;135,l;130,2;130,l;129,7;129,5;129,l;128,9;128,8;46,2;45,9;45,8;44,7;433;43,l;42,6;42,3;36,O;33,9;33,8;…”
Section: (M 20h) Ms: 195 (1 [M-no]')unclassified
“…This procedure represents one of the most exploited methods to prepare such difunctionalized derivatives that find a number of applications in the synthesis of important target molecules. The Michael addition of nitroalkanes to electron-poor olefins can be realized using basic promoters such as DBU, 27 TMG, 28 triphenylphospine, 29 fluoride salts 30 and hydroxide (alkoxide) anions. [31][32][33][34] Besides these procedures that work in homogeneous conditions a number of methods using basic catalysts that operate in heterogeneous systems can be employed profitably to carry out a conjugate addition.…”
Section: Synthesis Of 14-dicarbonyls Using a Conjugate Addition-nef mentioning
confidence: 99%